Tired, weak, or in need of rest: fatigue among general practice attenders. Issue 6762 (24th November 1990) - David, A; Pelosi, A; McDonald, E; Stephens, D; Ledger, D; Rathbone, R; Mann, A
Abstract : OBJECTIVES--To determine the prevalence and associations of symptoms of fatigue. DESIGN--Questionnaire survey. SETTING--London general practice. PARTICIPANTS--611 General practice attenders. MAIN OUTCOME MEASURES--Scores on a fatigue questionnaire and reasons given for fatigue. RESULTS--10.2% Of men (17/167) and 10.6% of women (47/444) had substantial fatigue for one month or more. Age, occupation, and marital status exerted minor effects. Subjects attributed fatigue equally to physical and non-physical causes. Physical ill health, including viral infection, was associated with more severe fatigue. Women rather than men blamed family responsibilities for their fatigue. The profile of persistent fatigue did not differ from that of short duration. Only one person met criteria for the chronic fatigue syndrome. CONCLUSIONS--Fatigue is a common complaint among general practice attenders and can be severe. Patients may attribute this to physical, psychological, and social stress.